Niels Bohr and the quantum atom the Bohr model of atomic structure 1913-1925 - Kragh, Helge, 1944- (Oxford : Oxford University Press, 2012)
'Niels Bohr and the Quantum Atom' gives a comprehensive account of the birth, development, and decline of Bohr's atomic theory. It presents the theory in a broad context which includes not only its technical aspects, but also its reception dissemination, and applications in both physics and chemistry.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Bohr, Niels, -- 1885-1962.; Nuclear physics -- History